2018
DOI: 10.1002/job.2297
|View full text |Cite
|
Sign up to set email alerts
|

When does performance management foster team effectiveness? A mixed‐method field study on the influence of environmental extremity

Abstract: Organizations operating in extreme environments rely on teams to tackle the highly demanding and complex situations. This study aims to provide new insights into the management of such teams by exploring the influence of environmental extremity on the relationship between performance management and team effectiveness. Mixed-method and multilevel analyses of police teams working in different levels of environmental extremity suggest that environmental extremity moderates the relationship between performance man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 83 publications
1
13
1
Order By: Relevance
“…The challenging work environment of public sector organizations, such as police organizations, is characterized by ambiguous goals and pathways to these goals (Johnson, 2015; Van Thielen et al, 2018). Street-level bureaucrats face this ambiguity with discretion to create custom-fit solutions which might hinder the realization of organizational goals, particularly when they are not affectively committed to the organization.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenging work environment of public sector organizations, such as police organizations, is characterized by ambiguous goals and pathways to these goals (Johnson, 2015; Van Thielen et al, 2018). Street-level bureaucrats face this ambiguity with discretion to create custom-fit solutions which might hinder the realization of organizational goals, particularly when they are not affectively committed to the organization.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Building on previous research, we have chosen to focus on the effectiveness of police managers’ feedback quality for fostering affective commitment (e.g., Metcalfe & Dick, 2001; Perez et al, 2017). Police officers’ work environment is characterized by ambiguous goals (Van Thielen et al, 2018). From situation-to-situation, there may be different desired outcomes and different pathways to achieve these outcomes (Johnson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Two aspects of this paper are particularly noteworthy. First, van Thielen, Decramer, Vanderstraeten, and Audenaert () begin with an inductive, qualitative study to identify the features of performance management systems most valuable to fostering team development and effectiveness. From a set of 45 interviews with police team members, leaders of police departments, and human resource manager informants, four key performance management features emerged from the findings including (a) vertical alignment of goals with the department, (b) constructive feedback, (c) consistency across the process, and (d) two‐way communication.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%
“…Likewise, this relationship between in‐action TR and performance was moderated by team size such that in‐action TR had a stronger effect on performance in larger teams. Finally, van Thielen et al () found that the generally positive effects of vertical alignment and constructive feedback performance management features on police team performance weakened as environments became more extreme. Alternatively, consistency across the performance management process and two‐way communication during the process were only related to team performance for police teams operating in more extreme environments (i.e., those districts plagued by higher levels of public violence).…”
Section: Lessons Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation